Atlanto-occipital fusion: A case report - Monalisa; Subhendu Pandit; Rajan Bhatnagar (Medical Journal of Dr. D.Y. Patil University, 2015)
The atlas is the first cervical vertebra. In the history of anatomy, due to its primary function of supporting the skull, it has been innumerably compared with Atlas the Greek God, who holds the globe of the earth on his shoulders. This vertebra is devoid of a body and has two prominent lateral masses bearing a pair of superior concave facets and inferior smooth facets each. Atlanto-occipital fusion may be unilateral or bilateral, complete or incomplete and symptomatic or asymptomatic. In our, case atlanto-occipital fusion was observed in the skull of a male cadaver. Our study will be of significance to clinicians in the specialties of radiodiagnosis, orthopedics, neurosurgery and anesthesiology. Because of a lack of knowledge of developmental malformation in the craniocervical region, sudden death can occur during clinical manipulation. Head and neck surgeons must keep in mind that such anomaly can exist without any prior symptoms. The specimen seen represents a case of congenital fusion. The articular processes of the specimen are fused between the occipital and the atlas bones. Atlanto-occipital fusion decreases the diameter of the foramen magnum and produce neurovascular symptoms.